A striking new species of phytotelm-breeding tree frog (Anura: Rhacophoridae) from central Vietnam - Rowley, Jodi J.l.; Le, Duong Thi Thuy; Dau, Vinh Quang; Hoang, Huy Duc; Cao, Trung Tien (Zootaxa, 2014)
We describe a distinctive new species of phytotelm-breeding rhacophorid frog from central Vietnam. Gracixalus lumarius sp. nov. is distinguished from all other rhacophorids in Indochina by a combination of (1) medium body size (adult males 38.9–41.6 mm; adult female 36.3 mm), (2) dorsum brown diurnally and yellow nocturnally, (3) venter pink, (4) tympanum and supratympanic fold indistinct (5) iris dark gold with a dense, relatively uniformly distributed network of black reticulations, (6) dorsum with distinctive white conical tubercles in males, and (7) eggs deposited on wall of a phyptotelm. The new species is known from montane bamboo and montane evergreen forest in Ngoc Linh Nature Reserve in Kon Tum Province, between 1845–2160 m elevation.